2016
DOI: 10.3109/01902148.2016.1145307
|View full text |Cite
|
Sign up to set email alerts
|

Models of PaO2response to the continuous distending pressure maneuver during high frequency oscillatory ventilation in healthy and ARDS lung model pigs

Abstract: The PaO2 curve may give information about the level of recruitment of alveoli, but cannot be used for optimization of CDP level during HFOV in healthy and ARDS lung model pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…The shape of the curve of PaO 2 with increased MAP steps in our study is similar to that found in other reports using surfactant deficiency models 31,32 . In both cases, the intensity of the change in PaO 2 levels after MAP modifications, instead of the absolute PaO 2, value was considered as a lung recruitment marker.…”
Section: Discussionsupporting
confidence: 87%
“…The shape of the curve of PaO 2 with increased MAP steps in our study is similar to that found in other reports using surfactant deficiency models 31,32 . In both cases, the intensity of the change in PaO 2 levels after MAP modifications, instead of the absolute PaO 2, value was considered as a lung recruitment marker.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, we also reported that RIP may be of additional value during pediatric HFOV [15]. In our present study, we found that oxygenation improved not only in responsive, but also unresponsive lung volume optimization maneuvers, challenging if oxygenation is a good bedside marker for lung volume changes as also has been observed during CMV [28,29]. It has also been proposed that a decrease in blood pressure might be perceived as sign of lung overdistension and may thus be used as a parameter guiding the lung volume optimization maneuver.…”
Section: Discussionsupporting
confidence: 70%
“…An example of such a maneuver, and thus a possible advantage of using the relative compliance determination, is optimizing CDP in the initial phase of HFOV or its reassessment during the course of ventilation. Another advantage of relative compliance determination could be evaluating efficiency of recruitment maneuver, commonly implemented as a stepwise increase and consequent decrease of CDP, while evaluating influenced physiological parameters [42]. In these situations, when a constant airway inertance and resistance can be assumed, observing a short-time trend of relative compliance gives a faster response than standard methods that utilize assessment of the respiratory gas exchange.…”
Section: Discussionmentioning
confidence: 99%